Analysis of 5-year clinical and radiological outcomes in patients with psoriatic arthritis observed as part of the Treat to target strategy. Preliminary data - P. O. Tremaskina; E. Yu. Loginova; T. V. Korotaeva; S. I. Glukhova; A. V. Sukhinina; A. V. Smirnov; A. M. Lila (Современная ревматология)
Objective: to analyze preliminary data on 5-year clinical and radiographic outcomes in patients with early psoriatic arthritis (PsA) observed as part of the Treat to target (T2T) strategy.Patients and methods. We examined 37 patients (18 men and 19 women) with early PsA who met the CASPAR criteria (2006), who received treatment according to the principles of the T2T strategy for 24 months. The mean age of the patients was 43.3±11.7 years, the median (Me) of PsA duration was 72 [60; 90] months, psoriasis – 120 [88; 180] months, follow up – 62 [51; 81] months. After completion of participation in the T2T strategy, patients were followed up in a real clinical setting. Most of the patients used methotrexate, biologic disease modifying antirheumatic drugs and non-steroidal anti-inflammatory drugs. In the dynamics after 5 years, PsA activity was determined by the DAPSA index and the achievement of the minimum disease activity (MiDA). In 16 (43%) patients, a dynamic assessment of radiographic changes in the joints of the hands and feet was performed using the Sharp quantitative method modified for PsA (m-Sharp/vanderHeijde).Results and discussion. By 24 months of therapy (the end of the T2T study), DAPSA remission was registered in 19 (52%) patients, in the same number of cases (16%) low (LDA), moderate (MDA) and high (HDA) disease activity was noted. Me DAPSA was 3.85 [0.67; 21.76], MiDA was detected in 22 (59.5%) patients. After 5 years of observation, Me DAPSA was 7.67 [2.2; 14.5]. Remissions according to DAPSA were achieved in 13 (35%) patients, LDA – also in 13 (35%), MDA – in 5 (14%), HDA remained in 6 (16%), MiDA – in 20 (54%). No significant differences were found when comparing disease activity at 24 months (at the end of the T2T study) and after 5 years of follow-up (p=0.41). In 11 (69%) out of 16 patients after 5 years, a negative trend was recorded in the assessment of radiological progression.Conclusion. After 5 years of follow-up, 70% of patients with PsA treated at an early stage of the disease as part of the T2T strategy achieved remission or LDA, and 54% of patients remained in MiDA. In 69% of patients, despite the achievement of remission and MiDA, there was a negative radiological dynamic in the hands and feet.